A degrowth approach to urban mobility options: just, desirable and practical options. Issue 4 (3rd April 2022) - Cattaneo, Claudio; Kallis, Giorgos; Demaria, Federico; Zografos, Christos; Sekulova, Filka; D'Alisa, Giacomo; Varvarousis, Angelos; Conde, Marta
ABSTRACT: Following Illich's (1974) notion of convivial tools and the distinction he makes between "self-propelled transit" and "motorized transport" of mobility, we apply the emerging paradigm of degrowth to urban mobility. Based on the degrowth literature and Illich's work, we derive principles and criteria for the mobility of a degrowth society that include institutional, energy and material use, infrastructure, local environmental impacts, social impacts and justice, proximity and speed, and autonomy. To ground our analysis in real-world conditions, we consider the practical perspective of mobility and add another set of criteria: comfort and safety, travel time, monetary cost, and health. We then compare urban mobility options, including recently developed hybrid mobility and sharing schemes. Our results show that, although private means have an advantage in terms of personal practicality, they are not desirable from a degrowth perspective, due to their high social and environmental costs and as constituting a source of urban injustice. Public, hybrid, and self-propelled mobility options would become more practical if such injustices were recognised, and if effective public policies challenged the radical monopoly of cars. Further, hybrid options and sharing/pooling schemes have the potential to reduce the use of private means for metropolitan mobility. The adoption of this degrowth framework can enrich debates on sustainable urban mobility and moves beyond the common proposition of promoting public transport as the solution. GRAPHICAL ABSTRACT: UF0001